An efficient HARQ scheme for applications in multicast communication systems. Issue 7 (5th July 2013) - Chiti, Francesco; Fantacci, Romano; Tassi, Andrea
Abstract This paper deals with the performance evaluation and optimization of an efficient hybrid automatic repeat request (HARQ) scheme suitable for applications delivered over lossy multicast communication channels. In particular, different from previously investigated strategies, this paper proposes a modified HARQ scheme based on the symbol combining principle (MHARQ‐SC) where multiple copies of a same packet are consecutively transmitted at each transmission opportunity. By considering as the performance metrics, the mean packet delivery delay, and the energy consumption per information packet, this paper presents suitable performance evaluation and optimization strategies tailored for multicast communications. For the sake of comparisons, it has been also analyzed, under the same operational conditions, the performance of different HARQ schemes optimized for multicast communications. Numerical results have been provided to validate the proposed performance evaluation and optimization approaches in the case of the MHARQ‐SC scheme. An important result devised here is that the reported analytical results clearly highlight the performance gain of the proposed strategy in comparison with all the other considered alternatives. Copyright © 2013 John Wiley & Sons, Ltd.